Desenvolvimento de pão livre de glúten com adição de farinha de yacon - Andrade, Taislaine da Silva de (2018)
Bread is one of the staple foods that are most present at the table of consumers in the world. In its production, gluten is a determinant factor in the rheological characteristics of the mass, essentially for volume and texture, due to the ability of gas retention and the formation of a strong protein network by virtue of its viscoelastic property. Despite its important properties in the mass, some people may be intolerant to gluten or still possess celiac disease, which is a permanent intolerance to gluten. Thus, the only way to avoid the damage caused by gluten intake is to follow a strict gluten-free diet. Yacon is rich in dietary fibers, mostly fructose, which may contribute to the proper functioning of the intestine. Therefore, the objective of this study was to prepare breads using different concentrations of yacon and to evaluate the texture of these formulations by the texturometer, and the preference of through the preference sorting test. Four formulations (F1, F2, F3 and F4) were developed. F1 with 100% rice flour, standard and the others were substituted for rice flour for yacon flour in the proportions of 25%, 50% and 75%, formulations F2, F3 and F4. The specific volume of the loaves varied between 1.94 and 2.15 cm3/g. Sensory tests were performed with 40 untrained testers. The formulation with 25% (F2) of yacon in the composition, obtained more preference among the tasters. The sample with 75% (F4) of yacon presented the lowest preference, with comments such as "too wet", "bad texture". Relating the instrumental analysis of texture to the sensorial analysis of the samples, it was observed that the higher hardness value of the F2 formulation was a determining factor for its preference, due to its greater firmness, which reinforces that the softness determined by the texturometer for the 50% (F3) and 75% (F4) yacon samples, were the result of the undesirable characteristics reported by the sticky and wet tasters.